Development of Excellence in Sugihwaras Village "Kampoeng Konveksi": Career Guidance Through Patchwork Craft Training - Indah Zahro; Fatma Amirul Fadlillah; Nanda Sania Ni’matul Ulya; Hestiyana Vica Aprilia; Ina Nopia Dinta Lestari (DEVOTIONIS, 2026)
This community service aims to develop the advantages of the "Kampoeng Konveksi" of Sugihwaras Village, Bojonegoro Regency with a career guidance program through patchwork training. Sugihwaras Village is known as Kampoeng Convection because most of the people have sewing skills and a home convection business. In the convection business, pieces of fabric called patchwork remain. Large quantities of patchwork that have not been utilized optimally are potential that wants to be processed and developed. The method carried out in this service is ABCD (Asset Based Community Development), with several stages, namely inculturation, discovery, design, definition and reflection. The implementation of this career guidance was held together with the Sugihwaras Village government by carrying out patchwork craft training. Career guidance through this training aims to improve skills, change people's perspective on patchwork as a productive asset, and encourage the birth of creative product innovation. As a result, the activity succeeded in improving the skills of residents, motivating the entrepreneurial career spirit, and producing a new community, namely the Sugihwaras Perca Gallery which functions as a forum for the sustainability of the program. Thus, the implementation of service not only has a short-term impact, but also opens up opportunities for sustainable creative economy development.